Galūnių darybos veiksmažodžių abstraktai M. Daukšos Postilėje - Ambrazas, Saulius (Baltistica, 1980)
Verbal abstracts—flexional derivatives in M. Daukša’s “Postilė” Some characteristic derivational and semantic features of verbal abstracts—flexional derivatives in M. Daukša’s „Postilė“ (DP) are discussed and greater productivity of derivatives with flexion -ia (about 14%) is stated. Most flexional derivatives in DP are archaisms, among them nepajauta “indifference”, neprievaizda “hatred”, atãdovanis “reward”, núobylis “agreement”, ãpžvilgis “respect”, pérlydis “permission”, ìškalbė “reproach” are attested only in DP. The analysis of relations of flexional derivatives to the ground verbs in DP reveals some differences in comparison with modern Lithuanian, ef. paliáuba “cessation” (: paliáubyti, m. L. paliáuti), sándara “agreement, accord” (: suderė́ti, m. L. sudarýti), ãtžvilgis “respect” (: atžvilgė́ti (s), m. L. atsižvel̃gti). On the ground of the derivations kliáudžia “error”: kliáudėti, nuodžià “sin”: nusidė́ti а. о. the existence of the derivative suffix *-dja in Lithuanian seems doubtful. From the semantic view-point the flexional derivatives of DP are distinguished by the better preservation of the derivative processual meaning (cf. mū̃šis “beating”, núolaida “setting down (of the sun)”, žinià, pažinia “knowledge”, maldà “begging”), which is manifested too by comparing flexional derivatives with the corresponding derivatives, formed with the suffix -imas (-ymas).